2012
DOI: 10.1680/bbn.12.00008
|View full text |Cite
|
Sign up to set email alerts
|

Peptides to bridge biological-platinum materials interface

Abstract: Peptides with inorganic materials recognition already started to impact a wide range of surface-related technologies ranging from biomonitoring to biomedical areas. Combinatorial biology-based libraries are the initial step in tempting the directed evolution of peptides with specific interactions towards technologically relevant materials. Here, a case study is provided to demonstrate the specific peptide binding and the amino acids residues that play an important role for platinum surface affinity by combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The broader metal binding ability of glutamine was further described for copper [58], whereas Chiera et al could even show a major impact of glutamine residues and its H-bonds on the stability of copper-binding peptides [59]. Glutamine was also described to be involved in the surface binding and structure forming of platinum-binding peptides [60] Furthermore, it is described as being abundant in the coordination spheres of metal ions [61,62]. Mitsui et al discovered the QxQ motif in zinc fingers [63].…”
Section: Qxq Motif: Metal-and Oxyanion Interactionmentioning
confidence: 99%
“…The broader metal binding ability of glutamine was further described for copper [58], whereas Chiera et al could even show a major impact of glutamine residues and its H-bonds on the stability of copper-binding peptides [59]. Glutamine was also described to be involved in the surface binding and structure forming of platinum-binding peptides [60] Furthermore, it is described as being abundant in the coordination spheres of metal ions [61,62]. Mitsui et al discovered the QxQ motif in zinc fingers [63].…”
Section: Qxq Motif: Metal-and Oxyanion Interactionmentioning
confidence: 99%
“…Using a unique representation of data and conventional bioinformatics tools, the authors also discovered tiny synthesizers from selected peptides that catalyze solid materials synthesis, e.g., gold, silica, and hydroxyapatite, from ionic precursors. 11,12 The phage display selection procedure for biomacromolecules is well-established. But the technique can achieve even further improvement in selectivity by integrating simple modifications into the biopanning protocol (e.g., counter-selection step, material specificity testing, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…2,7,13,14 Detailed procedures, therefore, are developed for a particular inorganic material in the powder, thin-film, or in single crystal forms and are demonstrated in numerous publications. 9,12,[15][16][17] The selected number of peptides has conventionally been small in the literature, up to a few tens of SBPs. 9,15 The authors ensure that in any SBP-selection, the number of GEPI identified for a given material (either used as a single crystal or a powdered form) are at least 35 (with an average of 50, max 96 peptides).…”
Section: Introductionmentioning
confidence: 99%
“…3,4,7,12 Among nature's indispensable repertoire, enzymes, due to their exquisite catalytic features, are certainly one of the most appealing candidates to be utilised as an internal component in next-generation devices. 9,12,14 However, their spatial distribution with the desired orientation on the solid surfaces, operational stability and long-term reuse are among the critical parameters that limit their wide-range integration to functional materials. 2,[10][11][12][13][14][15] There is an urge to develop biological surface functionalisation approaches that will give the ability to control the desired functions at the bio-nanomaterial interfaces with tunability over a multitude of scales.…”
Section: Introductionmentioning
confidence: 99%